Synthetic Access to 1,3-Butadiynes via Electro-redox Cuprous-Catalyzed Dehydrogenative Csp–Csp Homocoupling of Terminal Acetylenes - Krishnan, Murugan; Kathiresan, Murugavel; Praveen, Chandrasekar (Synthesis, 2023)
Herein, we disclose the oxidative homocoupling of terminal alkynes under electrochemically generated cuprous catalysis. The scope of this protocol was established by preparing an array of structurally and electronically different 1,3-butadiyne derivatives. Good synthetic yields, functional group tolerance, oxidant-free conditions, and no cross-selectivity are some of the intrinsic advantages of this methodology. The developed chemistry features the electro-redox formation of copper acetylide, an intermediate appropriate for the Csp–Csp coupling step. The chemical state of copper in the acetylide intermediate was found to be Cu(I), as confirmed by click trapping experiments, cyclic voltammetry, EPR spectroscopy, and XPS. A competition reaction to determine the reactivity of electronically dissimilar acetylenes revealed that the product ratio is rather dependent on the electronic nature of the alkynyl substituents. To highlight the synthetic value of the products, selected diynes were subjected to chemical diversification.
Keywords: electro-redox chemistry; cuprous catalysis; Glaser–Hay coupling; homoselectivity; 1,3-butadiynes